Safety professional's reference and study guide - Yates, W. David (Boca Raton : CRC Press, 2011)
"Written as a reference and study guide for candidates preparing to take the Board of Certified Safety Professional's exam, this book provides technical information needed for the test. It covers topics such as math review, ventilation, noise, gases and particulates, radiation, toxicology, industrial hygiene, biological hazards, thermal stressors, statistics, fire protection and prevention, accident investigation, mechanics, hydrostatics and hydraulics, electrical safety, engineering economy and worker's compensation. The book provides step-by-step instructions on how to solve the equations and formulas on the exam and gives examples on how and when to use them"--
1. Safety profession and preparing for the ASP/CSP examination -- 2. Regulations and OSHA record keeping -- 3. Math review -- 4. Particulates and gases -- 5. Toxicology -- 6. Industrial hygiene -- 7. Ventilation -- 8. Noise and OSHA's hearing conservation program -- 9. Biological hazards -- 10. Fire protection and prevention -- 11. Thermal stressors -- 12. Personal protective equipment -- 13. Statistics for the safety professional -- 14. Electrical safety -- 15. Mechanics -- 16. Hydrostatics and hydraulics -- 17. Training -- 18. Engineering economics -- 19. Management theories -- 20. Accident causation and investigation techniques -- 21. Worker's compensation -- 22. Ergonomics -- 23. Construction safety -- 24. Risk management -- 25. Hazardous materials management -- 26. Radiation safety.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Industrial safety -- Examinations -- Study guides; Electronic books